2020
DOI: 10.1016/j.jprot.2020.103672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high dietary plant protein with or without marine ingredients in gut mucosa proteome of gilthead seabream (Sparus aurata, L.)

Abstract: Impact of high dietary plant protein with or without marine ingredients in gut mucosa proteome of gilthead seabream (Sparus aurata, L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 98 publications
(133 reference statements)
2
18
0
Order By: Relevance
“…In phase II (up to 250 g), there were no signi cant differences between experimental groups (FM and PP), thus supporting that older sh are more tolerant to diet plant proteins than sh in earlier growth stages [16]. It is noteworthy the lack of in ammatory response in PP* group (short PP exposure), supporting that PP long term feeding has deeper alterations in sh gut and contributes to changes in the microbiota and an increase of sh mortality [32], in agreement with previous studies [33,67,68],…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In phase II (up to 250 g), there were no signi cant differences between experimental groups (FM and PP), thus supporting that older sh are more tolerant to diet plant proteins than sh in earlier growth stages [16]. It is noteworthy the lack of in ammatory response in PP* group (short PP exposure), supporting that PP long term feeding has deeper alterations in sh gut and contributes to changes in the microbiota and an increase of sh mortality [32], in agreement with previous studies [33,67,68],…”
Section: Discussionsupporting
confidence: 89%
“…In so far as de cient diets could be considered a stress factor, long term feeding could determine suppressive or depressive effects on the immune mechanisms [24,28,32,33]. The down-regulation of mRNA expression of some immune related genes with the increased plant proteins in the diet has also been reported in other species [69].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The findings of the present study suggest that the fish gut response to the total dietary substitution of fish meal by plant protein meals differs between short- and long-term feeding and the fish size. In addition, previous studies in vivo carried out with seabream demonstrated that the use of plant proteins induced significant alterations of the gut microbiota, gut gene expression, and gut proteomic profile [ 33 , 34 , 35 ]. Nonetheless, these alterations can be affected to a different extent by the feeding period or fish stage.…”
Section: Discussionmentioning
confidence: 99%